Determining potential terrestrial arthropod predators of Ixodes ricinus using molecular methods - Sippola, Ella (My University, 2019)
The sheep tick, Ixodes ricinus (Linnaeus, 1758) serves as a vector for a variety of medically important zoonotic diseases. In both Finland and neighboring Sweden and Norway its abundances have increased and a northward shift in its distribution has been recorded. Despite the health concerns related to the species, relatively little is known of its natural enemies. In this thesis, real-time quantitative PCR (qPCR) was used to determine whether common soil-dwelling arthropod predators (carabids, ants, harvestmen and spiders) feed on I. ricinus. Predators were collected on two tick-abundant islands in SW Finland between May and September 2017. From a total of 735 samples analysed with qPCR five were found positive for I. ricinus. Positive predators consist of a carabid, an ant and three harvestmen. Results indicate that I. ricinus are consumed by some of the studied arthropod predators, however, they do not seem to constitute an important part of the predators’ diet. Nevertheless, results shed more light into which species should be more intensely studied as I. ricinus predators.
Keywords: Ixodes ricinus, arthropod, quantitative real-time PCR, predation